The Implementation of Digital Entrepreneurship Learning in Higher Education: A Systematic Literature Review: Implementasi Pembelajaran Kewirausahaan Digital di Perguruan Tinggi: Tinjauan Pustaka yang Sistematis - Aysi, Siti Aenandari Hadatul; Susilaningsih, Susilaningsih; Sabandi, Muhammad (Pedagogia : Jurnal Pendidikan, 2024)
The phenomenon and topic of digital entrepreneurship learning remain popular for analysis in the era of digitization. Previous literature reviews discussed the context and concept of digital entrepreneurship only. This article presents a literature review aimed at facilitating the search for research publications on digital entrepreneurship, in order to understand the track record, learning models, the impact of implementing digital entrepreneurship learning, and future research opportunities. The article has used the Systematic Literature Review (SLR) method using the Scopus database. This article has used "digital entrepreneurship" keyword for search the resources in January 2014 to May 2023 period. The result of the literature screening process yielded 19 relevant journals. The results of the literature review indicate that research on this topic has shown a significant increase and has the potential to continue to grow. Digital entrepreneurship learning can be designed using experiential learning approaches or the Internet of Things (IoT) and technology approaches. The implementation gives an impact on business opportunities, entrepreneurial intention, innovation, entrepreneurial attitude, and student problem-solving. This study contributes to providing an overview of learning models that can be replicated or modified in future research. Highlights: Growing research on digital entrepreneurship education; impactful learning approaches identified. Experiential and IoT-based methods enhance digital entrepreneurship learning outcomes. Positive impact on business opportunities, innovation, and entrepreneurial skills observed. Keywords: Digital Entrepreneurship, Entrepreneurship Learning, Learning Model